Dose Rate Spatial Distribution Produced by the Pulsed X-Ray Source in the Radiographic Examination - Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Krasnykh A. A. Angelina Aleksandrovna; Wagner A. R. Aleksandr Rudolfovich (Radiation Technologies in Medicine, 2015)
Title screen